Effects of Health Policy on Children’s Physical Well-being in Morocco - Loudghiri, Khadija; Fazouane, Abdesselam (Advances in Social Sciences Research Journal, 2022)
Several international studies published by the authors and global bodies have highlighted the important role of child health policies in achieving Sustainable Development Goals (SDGs). In this article, we examine the impact of health policy on child well-being in Morocco. To evaluate child health progress, the Millennium Development Goals, indicators, and goals have been adopted. Moroccan children have been the focus of several health strategies, programs, and plans developed by the Ministry of Health within the framework of the five-year and three-year development plans. Other government departments have also developed plans for children and young people. However, these strategies, programs, and plans have been subject to many structural dysfunctions and have therefore not been able to achieve their intended objectives. Accordingly, the findings are consistent with the indicators and determinants of Moroccan children’s health, which show that certain aspects of their health have gaps due to inadequate governance. In conclusion, and in view of the results of these strategies, programs, and plans, it appears that Morocco does not yet have a genuine, comprehensive, effective, and efficient child health policy.